THE EFFECTIVENESS OF EDUCATIONAL VIDEO IN TEACHING VOCABULARY - Wijaya, Julianvita; Salam, Urai; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The main purpose of conducting this research was to investigate whether or not the effectiveness of educational video in teaching vocabulary to the eighth grade students of SMPN 4 Tanjung Raya 1 in academic year 2011/2012. For this purpose, the writer conducted a pre-experimental research by using educational video. The samples were the eighth grade students of SMPN 4 Tanjung Raya I, which consisted of 20 students. The tools used for collecting data were pre-test and post-test. The writer gave two treatments in different time.Â  The data showed that the score of post-test was higher than the score of pretest. The studentsâ€™ pre-test mean score was 39.5. So, the result of pre-test was classified as â€œPoorâ€. On the other hand, after giving the treatment, the studentsâ€™ post-test mean score was 72.25. It was classified as â€œGood to Excellentâ€. Moreover, the studentsâ€™ interval score of pre-test and post-test was 32.75. Therefore, it showed that there was a difference between score of pretest and post-test after treatment. In conclusion, this research proved that the use of educational video as the teaching media was effective to help students in mastering vocabulary. Key words: educational video, teaching vocabulary Abstrak: Tujuan dari penelitian ini adalah untuk mencari tahu apakah penggunaan dari video edukasi efektif dalam mengajarkan kosakata kepada murid kelas VIII SMPN 4 Tanjung Raya 1 di tahun akademis 2011/2012. Metodologi penelitian ini adalah pre eksperimental dengan mengunakan video edukasi. Sample dari penelitian ini adalah siswa kelas VIII SMPN 4 Tanjung Raya yang berjumlah 20 orang. Pengumpulan data mengunakan pre test dan post test. Penulis memberikan dua treatment yang berbeda di waktu yang berbeda. Berdasarkan data nilai dari post test lebih tinggi di bandingkan nilai pretest. Rata-rata nilai pretest 39,5, jadi hasil dari nilai pretest di klasifikasikan â€œrendahâ€. Di lain pihak setelah diberikan treatment, nilai rata-rata post test dari murid adalah 72,25. Hasil ini diklasifikasikan â€œbagus mendekati sempurnaâ€. Perbedaan dari pretest dan post test adalah 32.75. terlihat perbedaan antara nilai pretest dan post test setelah treatment. Dengan demikian, penelitian ini membuktikan penggunaan video edukasi sebagai media mengajar adalah efektifÂ  membantu murid dalam menguasai kosa kata. Kata kunci : video animasi, mengajarkan kosakata